2021
DOI: 10.1002/glia.24016
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of region‐specific transcriptional programs in mouse cerebellar and cortical astrocytes

Abstract: Astrocytes from the cerebral cortex (CTX) and cerebellum (CB) share basic molecular programs, but also form distinct spatial and functional subtypes. The regulatory epigenetic layers controlling such regional diversity have not been comprehensively investigated so far. Here, we present an integrated epigenome analysis of methylomes, open chromatin, and transcriptomes of astroglia populations isolated from the cortex or cerebellum of young adult mice. Besides a basic overall similarity in their epigenomic progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 92 publications
(169 reference statements)
2
6
0
Order By: Relevance
“…We calculated the regional variance of gene expression between NPCs and astrocytes from different regions (Fig. 2i) and found that FOXG1, OTX2, HOXB2, LHX2 as well as the ZIC- and IRX family define regionalization in both neuron and astrocyte populations, similar to observations in mouse and primary human tissue 2529 (Extended Data Fig. 5a-g).…”
Section: Resultssupporting
confidence: 64%
“…We calculated the regional variance of gene expression between NPCs and astrocytes from different regions (Fig. 2i) and found that FOXG1, OTX2, HOXB2, LHX2 as well as the ZIC- and IRX family define regionalization in both neuron and astrocyte populations, similar to observations in mouse and primary human tissue 2529 (Extended Data Fig. 5a-g).…”
Section: Resultssupporting
confidence: 64%
“…However, considering that the Mecp2 deficient brain suffers from complex molecular and functional defects, we believe that other indirect factors can participate to the described astrocyte heterogeneity. For instance, we can suggest that a diverse signature of DNA methylation might play a role in the heterogeneity among inter-regional astrocytes, as reported for cortical and cerebellar astrocytes ( Welle et al, 2021 ). Further, considering that a plethora of different post-translational modifications (PTMs) generates and regulates the functional versatility of MeCP2 ( Bellini et al, 2014 ), future studies should also investigate if different events of PTM affect Mecp2 functions in astrocytes.…”
Section: Discussionsupporting
confidence: 61%
“…At the epigenetic level, a wide range of transcriptionally active open chromatin is shared between GFAP + cortical astrocytes and Bergman glia ( Welle et al, 2021 ). Binding sites of the nuclear factor I (Nfi) family, known to promote astrocyte differentiation, are enriched in about 25% in these open chromatin regions.…”
Section: Astrocyte Maturationmentioning
confidence: 99%
“…Cortical astrocytes execute well specific transcriptional programs centralized around Lhx2 and FoxG1 that are epigenetically controlled. Even in the young adult mouse, astrocytes keep epigenetic marks from their region-restricted RGC specification ( Welle et al, 2021 ). By modeling astrogliogenesis from mouse stem cell coupled to next-generation sequencing and computational approaches, Tiwari and colleagues described regulatory elements and transcriptional programs underlying astrocyte generation and maturation as well as stage- and lineage-specific transcriptomic and epigenetic signatures.…”
Section: Astrocyte Maturationmentioning
confidence: 99%